Застосування фазі-регулятора в системі керування електроприводом штангової нафтовидобувної установки - Маляр, Анатолій Вікторович; Калужний, Богдан Семенович; Місюренко, Валерій Олексійович; Андреїшин, Андрій Сергійович (НТУ "ХПІ", 2010)
A control system of the electric drive of the deep-well rod pumping unit which involves fuzzy-regulator is proposed. The scheme of the control system and general output algorithm of the fuzzy-regulator are presented.
Application of fuzzy-regulator in the control system for the electric drive of the deep-well rod pumping unit
Keywords: установка помпова; електропривід частотно-керований; регулятор нечіткий; перетворювач частотний; програмований логічний контролер